Antifouling and pH-Responsive Poly(Carboxybetaine)-Based Nanoparticles for Tumor Cell Targeting - Ding, Feng; Yang, Shuang; Gao, Zhiliang; Guo, Jianman; Zhang, Peiyu; Qiu, Xiaoyong; Li, Qiang; Dong, Mingdong; Hao, Jingcheng; Yu, Qun; Cui, Jiwei (Frontiers in Chemistry, 2019)
Nanocarriers with responsibility and surface functionality of targeting molecules have been widely used to improve therapeutic efficiency. Hence, we report the assembly of pH-responsive and targeted polymer nanoparticles (NPs) composed of poly(2-(diisopropylamino)ethyl methacrylate) (PDPA) as the core and poly(carboxybetaine methacrylate) (PCBMA) as the shell, functionalized with cyclic peptides containing Arginine-Glycine-Aspartic acid-D-Phenylalanine-Lysine (RGD). The resulted polymer NPs (PDPA@PCBMA-RGD NPs) can maintain the pH-responsivity of PDPA (pKa ~6.5) and low-fouling property of PCBMA that significantly resist nonspecific interactions with RAW 264.7 and HeLa cells. Meanwhile, PDPA@PCBMA-RGD NPs could specifically target to αvβ3 integrin-expressed human glioblastoma (U87) cells. The pH-responsiveness and low fouling properties of PDPA@PCBMA NPs is comparable to PDPA@poly(ethylene glycol) (PDPA@PEG) NPs, which indicates that PCBMA is an alternative of PEG for low-fouling coatings. The advantage of PDPA@PCBMA NPs lies in the presence of carboxyl groups on their surfaces for further modification (e.g., RGD functionalization for cell targeting). The reported polymer NPs represents a new carrier that have the potential for targeted therapeutic delivery.